(untitled) (Orfeu, 2020)
The focus of interest for this article is the musical composition movement in Bahia, in so far as it enables a reflection on the interweaving of composition and cultural perspectives, not as isolated and autonomous domains, but as something inherent to composition. We will identify and reflect upon strategies to represent distance between distinct cultural poles, showing how they organize the musical form and fabric, in other words, the production of meaning. We start with an exemplary case provided by the piece Uma possível resposta op. 169 (1988) by the Brazilian composer (born in Switzerland), Ernst Widmer (1927-1990), and analyze similar strategies in other pieces, showing how the idea of establishing a distance which functions as a matrix of meaning responds to our interest in the connection between composition and culture, and permits a discussion of decolonization strategies present in the concert music produced in Bahia in recent decades.